The association of genetic alterations with response rate in newly diagnosed chronic myeloid leukemia patients. (March 2022) - Park, Hyunkyung; Kang, Sungbong; Kim, Inho; Kim, Sangsoo; Kim, Hyeong-Joon; Shin, Dong-Yeop; Kim, Dae-Young; Lee, Kyoo-Hyung; Ahn, Jae-Sook; Sohn, Sang-Kyun; Lee, Jeong-Ok; Cheong, June-Won; et al.
Highlights: Rapidity of response was associated with genetic alterations in immune cells. Genes associated with NK-cell showed significant differences according to the response. Innate immune system at diagnosis had an important role in treatment response in CML. Abstract: Genetic differences may be associated with the response to tyrosine kinase inhibitor (TKI) in patients with chronic myeloid leukemia (CML). In this study, we identified genetic alterations between rapid and slow responders ( BCR/ABL1 International Scale at 6 months: ≤0.1 % vs. > 0.1 %) of TKI treatment in chronic phase CML patients. Our analyses involved single nucleotide polymorphism (SNP), a Genome Wide Association Study and a Network-wide Association Study (NetWAS). Seventy-two patients from 16 institutions were enrolled and treated with a TKI, nilotinib. Gene Set Analysis identified genetic alterations in pathways related to the differentiation, proliferation, and activity of various innate immune cells. The NetWAS analysis found that genes associated with natural killer (NK) cells ( PTPRCAP, BLNK, HCK, ARHGEF11, GPR183, TRPV2, SHKBP1, CD2 ) showed significant differences between rapid and slow responders of nilotinib. However, we found no significantly different genetic alterations according to the response in the SNP analysis. In conclusion, we found that rapidity of response to TKI was associated with pathway-associated genetic alterations in immune cells, particularly with respect to NK cell activity. These results suggested that the innate immune system at initial diagnosis had an important role in treatment response in patients with CML.